Flux pinning and improved critical current density in superconducting boron doped diamond films. (6th April 2018) - Kumar, Dinesh; Samanta, Shibnath; Sethupathi, K; Rao, M S Ramachandra
Abstract: The ability to carry transport current in a magnetic field is the most important aspect of a superconductor. We present a detailed analysis of the upper critical field ( H c 2 (0)) and vortex dynamics in superconducting boron doped diamond (BDD) films. H c 2 (0) measured on the samples of different doping levels revealed a high critical field of up to 7.3 T. Pinning potential U 0, estimated using thermally activated flux-flow (TAFF) model shows that U 0 is of the order of 10 2 K. Self-field critical current density ( J c ) estimated for the superconducting BDD films showed large J c ∼ 10 7 A/cm 2 due to enhanced flux trapping.